Nuevos registros para la distribución geográfica de la serpiente cornuda mexicana esmeralda Ophryacus smaragdinus, en la zona centro del estado de Veracruz/ New distributional records of the Emerald Horned Pitviper Ophryacus smaragdinus, in central Veracruz - Martínez-Vaca León, Octavio León; Bello-Sánchez, Edgar Ahmed; Morales-Mávil, Jorge E. (Instituto de Ecología, A.C., 2016)
We present new records to the geographical distribution of Emerald Horned Pitviper Ophryacus smaragdinus, in the central part of the state of Veracruz. The locations of specimens were performed within ecosystems pine-oak forest and mountain cloud forest in four municipalities along of the Sierra Madre Oriental (Xico, Coacoatzintla, Rafael Lucio and Tlacolulan). The study contributes to knowledge about their ecology and geographical distribution in the state of Veracruz.